2018
DOI: 10.1515/jpm-2017-0184
|View full text |Cite
|
Sign up to set email alerts
|

Low dose aspirin for preventing fetal growth restriction: a randomised trial

Abstract: The purpose of this study was to investigate when in pregnancy to stop the administration of low dose aspirin (150 mg/daily) so as to prevent fetal growth restriction (FGR) A randomised, placebo-controlled study was designed. The patients were all screened positive using the Fetal Medicine Foundation (FMF) early pregnancy screening test for preeclampsia (PE) and FGR prediction. One hundred and fifty patients were enrolled and divided equally into three groups: A – the controls who received placebo treatment; B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…The inclusion criteria were met in 16 studies for a total of 18,907 participants. 7,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Thirty of the studies were excluded because data for preterm preeclampsia were not provided by the authors. Details of individual studies are given in the Appendix.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria were met in 16 studies for a total of 18,907 participants. 7,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Thirty of the studies were excluded because data for preterm preeclampsia were not provided by the authors. Details of individual studies are given in the Appendix.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…The quality of the included studies is shown in Figure 2; 8 studies were evaluated as being of good quality, 7,[17][18][19][20][21][22][23] and the other 8 studies were considered to be of poor or uncertain quality. 16,[24][25][26][27][28][29][30] There was high heterogeneity within studies (I 2 >50%) for preterm and term preeclampsia, but no heterogeneity was found in the subgroup of preterm preeclampsia when the onset of treatment was 16 weeks of gestation and the daily dose of aspirin was 100 mg (I 2 ¼0%). Publication bias cannot be excluded based on the analysis of the funnel plot (Figure 3).…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Seventy‐two reports from 68 trials met the inclusion criteria and were included in the systematic review (Figure ). Forty‐four trials reported on potential interventions for the prevention of FGR and 24 (29 studies) reported on interventions for the treatment of pregnancies affected by FGR. Five papers reporting outcomes from the DIGITAT trial and two from the TRUFFLE trial were included.…”
Section: Resultsmentioning
confidence: 99%
“…Enormous studies have been undertaken to reveal the usefulness of low-dose aspirin (LDA) or antioxidants for secondary and primary prevention of FGR [6, 7]. Although LDA is effective for primary prevention, if initiated before 16 weeks gestation [8, 9], there is still no treatment option for those recognized beyond 20 weeks.…”
Section: Introductionmentioning
confidence: 99%